A comparison of the sedimentary records of the 1960 and 2010 great Chilean earthquakes in 17 lakes: Implications for quantitative lacustrine palaeoseismology. Issue 5 (4th May 2015) - Van Daele, Maarten; Moernaut, Jasper; Doom, Lindsey; Boes, Evelien; Fontijn, Karen; Heirman, Katrien; Vandoorne, Willem; Hebbeln, Dierk; Pino, Mario; Urrutia, Roberto; Brümmer, Robert; De Batist, Marc; et al.
Abstract Seismically‐induced event deposits embedded in the sedimentary infill of lacustrine basins are highly useful for palaeoseismic reconstructions. Recent, well‐documented, great megathrust earthquakes provide an ideal opportunity to calibrate seismically‐induced event deposits for lakes with different characteristics and located in different settings. This study used 107 short sediment cores to investigate the sedimentary impact of the 1960 Mw 9·5 Valdivia and the 2010 Mw 8·8 Maule earthquakes in 17 lakes in South‐Central Chile (i.e. lakes Negra, Lo Encañado, Aculeo, Vichuquén, Laja, Villarrica, Calafquén, Pullinque, Pellaifa, Panguipulli, Neltume, Riñihue, Ranco, Maihue, Puyehue, Rupanco and Llanquihue). A combination of image analysis, magnetic susceptibility and grain‐size analysis allows identification of five types of seismically‐induced event deposits: (i) mass‐transport deposits; (ii) in situ deformations; (iii) lacustrine turbidites with a composition similar to the hemipelagic background sediments (lacustrine turbidites type 1); (iv) lacustrine turbidites with a composition different from the background sediments (lacustrine turbidites type 2) and (v) megaturbidites. These seismically‐induced event deposits were compared to local seismic intensities of the causative earthquakes, eyewitness reports, post‐earthquake observations, and vegetation and geomorphology of the catchment and the lake. Megaturbidites occur where lake seiches took place. Lacustrine turbidites type 2 can be the result of: (i) local near‐shore mass wasting; (ii) delta collapse; (iii) onshore landslides; (iv) debris flows or mudflows; or (v) fluvial reworking of landslide debris. On the contrary, lacustrine turbidites type 1 are the result of shallow mass wasting on sublacustrine slopes covered by hemipelagic sediments. Due to their more constrained origin, lacustrine turbidites type 1 are the most reliable type of seismically‐induced event deposits in quantitative palaeoseismology, because they are almost exclusively triggered by earthquake shaking. Moreover, they most sensitively record varying seismic shaking intensities. The number of lacustrine turbidites type 1 linearly increases with increasing seismic intensity, starting with no lacustrine turbidites type 1 at intensities between V½ and VI and reaching 100% when intensities are higher than VII½. Combining different types of seismically‐induced event deposits allows the reconstruction of the complete impact of an earthquake.